The popularity of tourism enclaves among students of Warsaw universities - Zawadka, Jan; Komar, Dominika (Turystyka i Rozwój Regionalny, 2023)
The study aimed to show the popularity of tourism enclaves as places of leisureamong students of Warsaw universities and to introduce motives, preferences, and behaviorsduring trips to such places. The research was conducted in 2023 among 291 students ofWarsaw universities. The method of research was a diagnostic survey with the use of thequestionnaire technique. Over 50% of the respondents did not rest in enclaves, which wasargued by high costs and crowds of tourists in such places. The most frequently indicatedreason for going to the enclave was the convenient and comprehensive organization of thetrip. The purpose of the trip was usually to relax by the water. Most of the respondents wereaware that the attractions presented in the enclave are commercialized and inauthentic, andtheir functioning carries several threats.